Facile synthesis of reduced graphene oxide and graphitic carbon nitride modified titanium dioxide nanospheres for photoanode of dye-sensitized solar cell - Chinnarani M.; Suresh S.; Prabu K.M.; Kandasamy M.; Pugazhenthiran N. (Elsevier B.V., 2025)
Titanium dioxide/reduced graphene oxide nanocomposites (TiO2/rGO NCs) have been broadly utilized as photoanode materials for dye-sensitized solar cell (DSSC). Nevertheless, photoelectric conversion efficiency (PCE) of DSSC is diminished due to recombination of charges takes place between photoanode and electrolyte interface. Herein, we have prepared a triplet structure nanocomposite composed of TiO2 nanospheres, rGO and graphitic carbon nitride (TiO2 NS/rGO/g-C3N4 NC) for photoanode of DSSC. The ternary TiO2 NS/rGO/g-C3N4 NC photoanode has enhanced dye absorption considerably and as a consequence, improved light harvesting efficiency. Besides, the introduction of rGO and g-C3N4 on the TiO2 NS has effectually speeded up the transport of electrons and minimized the recombination of photogenerated charges. Consequently, the DSSC integrated with ternary TiO2 NS/rGO/g-C3N4 NC photoanode has exhibited ?41 % increment in the PCE of 5.77 % when compared to PCE of the pristine TiO2 NS photoanode (4.10 %). This finding has proposed a simplistic approach to advance photovoltaic performance of the DSSC. ? 2023 Elsevier B.V.